O7 Can in-situ simulation be used to improve care of the acutely ill patient by enhancing interprofessional working within the primary care setting?. (November 2018) - Halls, Amy; Kanagasundaram, Mohan; Lau-Walker, Margaret; Diack, Hilary; Bettles, Simon
Abstract : Introduction: Acutely unwell patients in general practice are uncommon, but when they occur it requires intervention from the entire staff (clinical and non-clinical) working as a cohesive team. Despite the advantages of interprofessional education being well documented, there is little research evidence of this in the primary care setting. Primary care education has the tendency to be profession-specific with a siloed approach. Moreover, the inclusion of non-clinical colleagues (despite their close working relationship) seems even sparser. This project aims to improve care of the acutely ill patient by enhancing interprofessional working, using in-situ simulation. Methods: The first phase (January to March 2018) of this mixed methods evaluation study was to scope current education provision in GP practices within Health Education England Kent, Surrey and Sussex (HEEKSS) and the type of methods used. A questionnaire addressing current education and training provision was posted to 'the practice manager' of all 668 practices within HEEKSS. In the second phase (April to June 2018) a simulation of cardiac arrest will occur in three practices within HEEKSS, running for approximately 20 min and filmed. All staff will be involved in a group debrief session and individual semi-structured interviews regarding their participation. Results: The findings from phase 1 showed that the majority of practices ran training sessions involving all members of staff, predominantly focusing on basic life support (63 practices) and practice-specific areas such as managing difficult patients (28 practices). Regarding simulation, 61 practice managers said simulation was not used; 41 responded that it was used, with 37 specifying its use for basic life support training. Discussion and conclusion: The high number of practices running training sessions for all staff members is encouraging and shows the appropriateness and acceptability of developing and running a joint training simulation. The prevalence of simulation used within training sessions shows its mainstream acceptance and also that there is scope within primary care for its wider use. Combining this with the qualitative interview data following the phase 2 simulation will be used to develop and evaluate a simulation scenario that can run within a GP practice and allow the multiple clinical and non-clinical staff to work together.